Egg white peptides ameliorate dextran sulfate sodium-induced acute colitis symptoms by inhibiting the production of pro-inflammatory cytokines and modulation of gut microbiota composition. (30th October 2021) - Ge, Huifang; Cai, Zhuanzhang; Chai, Jiale; Liu, Jiyun; Liu, Boqun; Yu, Yiding; Liu, Jingbo; Zhang, Ting
Graphical abstract: Highlights: Pro-inflammatory cytokine levels negatively correlated with CPs concentration. CPs alleviated DSS-induced acute colitis symptom and repaired intestinal mucosa. CPs have the potential to modulate relative abundance of functionally microbiota. Abstract: Egg white peptides (EWPs) can be effectively used to alleviate and treat inflammatory diseases due to their anti-oxidation, anti-inflammation, and microbiota regulation capabilities. A dextran sodium sulfate (DSS)-induced colitis model was used to clarify the regulatory effects of EWPs on colitis. Forty-three peptide sequences were identified from EWPs using LC-MS/MS. The results demonstrated that EWPs decreased the levels of pro-inflammatory cytokines and the extent of crypt damage in a dose-dependent manner. 16S rRNA gene sequencing results indicated that 200 mg/kg EWPs significantly increased the relative abundance of beneficial bacteria Lactobacillus and Candidatus_Saccharimonas, and reduced the relative abundance of pathogenic bacteria Ruminiclostridium and Akkermansia. In addition, the degree of correlation between pro-inflammatory cytokines and microbiota was as follows: interleukin (IL)-1β > IL-8 > IL-6 > tumor necrosis factor-α To summarize, EWPs contributed to the alleviation of colitis symptoms and the intestinal injury through anti-inflammatory effects, repair of intestinal mucosa, and modulation of gut microbiota.